Effects of environmental cadmium and lead exposure on adults neighboring a discharge: Evidences of adverse health effects. (November 2015) - Cabral, Mathilde; Toure, Aminata; Garçon, Guillaume; Diop, Cheikh; Bouhsina, Saâd; Dewaele, Dorothée; Cazier, Fabrice; Courcot, Dominique; Tall-Dia, Anta; Shirali, Pirouz; Diouf, Amadou; Fall, Mamadou; et al.
Abstract: The purpose of the study was to determine Pb and Cd concentrations in humans and to assess the effect of co-exposure to these metals on biomarkers of oxidative stress and nephrotoxicity. Blood and urine levels of Pb and Cd, oxidative stress and urinary renal biomarkers were measured in 77 subjects neighboring a discharge and 52 in the control site. Exposed subjects showed significantly higher levels of lead and cadmium in blood and urine than the controls. Excessive production of reactive oxygen species induced by these metals in exposed subjects conducted to a decrease in antioxidant defense system (GPx, Selenium, GSH) and an increase in lipid peroxidation (MDA). Moreover, changes in markers of nephrotoxicity (high urinary concentrations of total protein, RBP and CC16, as well as GSTα and LDH increased activities) suggested the occurrence of discrete and early signs of impaired renal function for the discharge neighboring population. Graphical abstract: Highlights: Oxidative stress and early renal biomarkers assessment after Cd and Pb co-exposure. High Pb–B and Cd–U levels found in the subjects living near the discharge. Pb and Cd exposure induces depletion of the antioxidant defense system. Occurrence of early signs of renal function impairment following Pb and Cd exposure. Abstract : Exposure to landfill's emissions can induce adverse effects on various physiological functions and organs, and is therefore a source of risk for environment and human's health.